Use of deceased donors with anti-HBc-positive in liver transplantation - Freire, Janaína Maria Maia (2021)
Aim: To analyze the results of the use of grafts from donors with the anti-HBc–positive serological marker in liver transplantation recipients. Methodology: Retrospective study with 64 liver transplantation recipients who received grafts from anti-HBc-positive donors, between January 2002 and December 2017, in a university hospital in Fortaleza, CE. Data collection was performed with a custom-made instrument based on medical records, including demographic and clinical data, as the use of antiviral prophylaxis and the development of hepatitis B in the post-transplant period. The data were processed in SPSS with statistical analysis. Results: Males were predominant, the average age was 49.2 years, and the main indications for the transplantation were viral hepatitis B and C. Among the patients who were HBsAg-reactive (25/64) in the pre-transplant, only one presented detectable viral load in the post-transplant period. Among the HBsAg-nonreactive recipients (39/64), nine (23.07%) cases of de novo hepatitis B were observed, five of which had anti-HBs-reactive in the pre-transplant. All nine patients presented elevation of hepatic transaminases, and two died. Final considerations: For greater safety, some strategies are indicated, such as the preferential use of grafts from a donor with anti-HBc–positive in HBsAg-positive recipients, as the use of an appropriate prophylactic regimen and periodic serological follow-up in the post-transplant period.